Pengaruh Budaya Organisasi, Persepsi Dukungan Organisasi dan Reward Terhadap Kepuasan Kerja di Primary School XYZ - Rebecca Paulina Aurelia (Jurnal Ketopong Pendidikan, 2024)
Job satisfaction is an important concern for many organizations today. It is because of job satisfaction give impact to the employees’ performance in the organization. Job satisfaction can be affected by several factors, such as organizational culture, perceived organizational support and reward. To improve the satisfaction of workers in the Primary School XYZ, this research needs to be done. This research used quantitative approach and path analysis as its method. The subjects of this research are 41 teachers in Primary School XYZ. This research used SmartPLS 3.0 for data processing. From the result of data processing found that (1) organizational culture has a positive effect on job satisfaction, (2) perceived organizational support has a positive effect on job satisfaction and (3) reward has a positive effect on job satisfaction.